Space operations : contributions from the global community - Cruzen, Craig A.; Schmidhuber, Michael; Lee, Young H.; Kim, Bangyeop (Springer, 2017)
This book includes a selection of 30 reviewed and enhanced manuscripts published during the 14th SpaceOps Conference held in May 2016 in Daejeon, South Korea. The selection was driven by their quality and relevance to the space operations community. The papers represent a cross-section of three main subject areas: · Mission Management - management tasks for designing, preparing and operating a particular mission. · Spacecraft Operations - preparation and implementation of all activities to operate a space vehicle (crewed and uncrewed) under all conditions. · Ground Operations - preparation, qualification, and operations of a mission dedicated ground segment and appropriate infrastructure including antennas, control centers, and communication means and interfaces. This book promotes the SpaceOps Committee's mission to foster the technical interchange on all aspects of space mission operations and ground data systems while promoting and maintaining an international community of space operations experts.
Keywords: Astronautics -- Congresses.; Aerospace engineering -- Congresses.; Ground support systems (Astronautics) -- Congresses.; Space flight -- Planning -- Congresses.; Outer space -- Exploration -- Congresses.; Outer space.; elektronické knihy; electronic books